2020
DOI: 10.1007/s10803-020-04782-z
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Using Cognitive Screeners in Autistic Adults

Abstract: You will be contacted as soon as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…Based on cross‐sectional studies, there is some indication of increasing age‐related cognitive problems that could be indicative of MCI or dementia among autistic adults, though evidence is mixed thus far. For example, in two studies using the same performance‐based screening task, one found more features of MCI among autistic adults than non‐autistic adults (Powell et al, 2017: ages 30–67 years, ASD group n = 29) whereas the other did not (Groot et al, 2021: ages 30–73 years, ASD group n = 51). In the study that identified increasing age‐related cognitive problems on a performance‐based measure of MCI, there were no differences between autistic and non‐autistic younger adults, suggesting that the diverging associations between age and performance were unlikely due to cognitive differences in ASD present earlier in development (Powell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on cross‐sectional studies, there is some indication of increasing age‐related cognitive problems that could be indicative of MCI or dementia among autistic adults, though evidence is mixed thus far. For example, in two studies using the same performance‐based screening task, one found more features of MCI among autistic adults than non‐autistic adults (Powell et al, 2017: ages 30–67 years, ASD group n = 29) whereas the other did not (Groot et al, 2021: ages 30–73 years, ASD group n = 51). In the study that identified increasing age‐related cognitive problems on a performance‐based measure of MCI, there were no differences between autistic and non‐autistic younger adults, suggesting that the diverging associations between age and performance were unlikely due to cognitive differences in ASD present earlier in development (Powell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The limited work that has been conducted examining cognitive decline in autistic adults has used validated, performance‐based measures to assess age‐related differences in cognition among autistic adults (Geurts & Vissers, 2012; Groot et al, 2021; Powell et al, 2017). No prior study has utilized a self‐report screener for dementia or experiences of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in cognitively able adults has used self and informant-report screeners of cognitive decline (e.g., the AD8, the IQCode-SF; [ 84 , 86 , 109 , 110 ]), with one study demonstrating convergent validity with a measure of memory problems [ 84 ]. However, future work is needed to continue to validate these screeners along with performance-based indicators of cognitive impairment (e.g., the Montreal Cognitive Assessment, MoCA; [ 111 ]), which have been used in autistic adults [ 92 , 112 ]. For adults with ID, a systematic review and evaluation of measures recommended screeners of cognitive decline/dementia that have primarily been developed for adults with Down Syndrome [ 113 ], except for the Dementia Screening Questionnaire for Individuals with Intellectual Disabilities (DSQIID; [ 114 ]), although the DSQIID has not been specifically validated for autistic adults with ID.…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ IQ was estimated using the vocabulary and matrix reasoning subtests from the Wechsler Abbreviated Scale of Intelligence (WASI-II) 57 , a widely used instrument to measure general intellectual abilities in ASD 58 60 . Cognitive state was assessed with the Montreal Cognitive Assessment (MoCA) 61 (Supplementary Material 2.1 ), a brief screening tool sensitive to cognitive dysfunction in adult ASD 62 , 63 . Executive functions were evaluated with the INECO Frontal Screening (IFS) 64 (Supplementary Material 2.2 ), a validated battery for the detection of executive-frontal dysfunction in adults with neuropsychiatric conditions 65 67 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, unlike previous studies on moral judgment in ASD [22][23][24][25] , we also matched the groups in cognitive state and executive functioning (Table 1) to control for potential confounding effects 3 . Participants' IQ was estimated using the vocabulary and matrix reasoning subtests from the Wechsler Abbreviated Scale of Intelligence (WASI-II) 57 , a widely used instrument to measure general intellectual abilities in ASD [58][59][60] 61 (Supplementary Material 2.1), a brief screening tool sensitive to cognitive dysfunction in adult ASD 62,63 . Executive functions were evaluated with the INECO Frontal Screening Experimental task.…”
Section: Methodsmentioning
confidence: 99%